Réponses

Meilleure réponse !
2014-09-23T20:41:33+02:00


Bonsoir, voici pour les deux premiers, après c'est la même chose pour les autres calculs, la distributivité :

A = (9x - 7)²

= (9x - 7)(9x - 7)

= 9x x 9x + 9x - 7 - 7 x 9x - 7 x (-7)

= 81x² - 56x - 63x + 49

= 81x² - 119x + 49
B = (x + 9)(11 - 5x)

= x x 11 + x x (- 5x) + 9 x 11 + 9 x (- 5 x)

= 11x - 5x + 99 - 45x

= - 39x + 99
C = (2x - 3)(2 x + 3)

= 2x x 2x + 2x x 3 - 3 x 2x - 3 x 3

= 4x² + 6x - 6x - 9

= 4x² - 9


D = (11 + 8x)²

= (11 + 8x)(11 + 8x)

= 11 x 11 + 11 x 8x + 8x x 11 + 8x x 8x

= 121 + 88x + 88x + 64x²

= 121 + 176x + 64x²


E = (x + 1)² + 7x (2-x)

= (x + 1)(x+1) + 7x (2-x)

= x² +1 x + 1x + 1 x 1 + 7x x 2 + 7x x -x

= x² + 16x + 1 - 7x²+ 16x + 1 - 6x²

F = (x+3)(2x - 1) - 3x (2x + 5)

=2x² - x + 3 x 2x + 3 x (-1) - 3x x 2x - 3x x 5

= 2x² + 5x - 3 - 6x² - 15x

= - 4x² - 10x - 3

G = (4t + 1)(4t -1) - (3t+ 2)²

= (4t + 1)(4t -1) - (3t+ 2)(3t + 2)

= 16t² + 4t x (-1) + 4t - 1 - 3t x 3t + 3t x 2 + 2 x 3t + 2 x 2

= 16t² - 1 - 9t² + 12t + 4

= 7t² + 3 + 12t

H = 2(s + 5)(s - 5) + (4s + 3)²
H = 2(s + 5)(s - 5) + (4s + 3)²
= 2s² - 50 + (4s + 3)(4s + 3)
= 2s² - 50 + 4s x 4ss + 4s x 3 + 3 x 4 + 3 x 3
= 2s² - 50 + 16s² + 24s + 9
= 18s² - 41 + 24s

I = (3x + 4)² - (1 - 2x)(6 + x)
= 3x + 4)(3x + 4) - (1 - 2x)(6 + x)
= 3x x 3x + 3x x 4 + 4 x 3x + 4 x 4 - 1 x 6 + 1x - 2x x 6 - 2x²
= 9x² + 24x + 10 - 11x - 2x²
= 7x² + 13x + 10